2016
DOI: 10.1177/1753425916656765
|View full text |Cite
|
Sign up to set email alerts
|

Differential free fatty acid receptor-1 (FFAR1/GPR40) signalling is associated with gene expression or gelatinase granule release in bovine neutrophils

Abstract: Fatty acids have been recognized as regulators of immune function in addition to their known metabolic role. Long-chain fatty acids bind free fatty acid receptor (FFAR)-1/GPR40, which is expressed on bovine neutrophils, and increase responses such as granule release and gene expression. In this study, we investigated the molecular mechanisms governing the up-regulation of cyclooxygenase-2 (COX-2) and IL-8, as well as matrix metalloproteinase (MMP)-9 granule release in FFAR1/GPR40 agonist-stimulated neutrophils… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
38
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 57 publications
(94 reference statements)
2
38
0
3
Order By: Relevance
“…Additionally, EET regulation of Cx43 and COX-2 requires ERK phosphorylation (11,12). Activation of GPR40 also stimulates ERK phosphorylation in several cell types (38,51,52). We observed that the GPR40 antagonist GW1100 and GPR40 targeted siRNA and the MEK inhibitor U0126 blocked 11,12-EET-induced ERK phosphorylation in HUVECs.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Additionally, EET regulation of Cx43 and COX-2 requires ERK phosphorylation (11,12). Activation of GPR40 also stimulates ERK phosphorylation in several cell types (38,51,52). We observed that the GPR40 antagonist GW1100 and GPR40 targeted siRNA and the MEK inhibitor U0126 blocked 11,12-EET-induced ERK phosphorylation in HUVECs.…”
Section: Discussionmentioning
confidence: 52%
“…In neutrophils, activators of GPR40 increase COX-2 expression by decreasing the endogenous NFκB inhibitor IκB (51). The increase in COX-2 and decrease in IκB were blocked by GW1100 and inhibitors of MEK.…”
Section: Discussionmentioning
confidence: 96%
“…Several studies have revealed that in breast cancer cell lines, the ERK1/2 and PI3K pathways are involved in proliferation; in part via FFA1 [29]. In addition, numerous observations suggested FFA1/ERK1/2 activation exhibited anti-apoptotic function [30], supported neuronal survival [10] and memory, induced osteocyte apoptosis [31] and had anti-inflammatory effects such as granule release and gene expression in neutrophils [32]. As a consequence, there is significant interest in understanding ERK1/2 signaling.…”
Section: Discussionmentioning
confidence: 99%
“…There is growing evidence indicating that the FFA1 downstream ERK1/2 signal pathway participates in the regulation of various physiological functions [10, 3032]. For better understanding of the specific mechanism of FFA1-mediated ERK1/2 activation, we examined the time course of ERK1/2 phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…Rapid recruitment of neutrophils and efficient chemotaxis to sites of infection are essential preludes to neutrophil function and clearance of bacteria. Intriguingly, GW9508 treatment can induce IL-8 release from bovine neutrophils ( 22 ). This chemokine is a powerful attractant for both neutrophils and monocytes and may explain why higher numbers of these leukocytes are recruited to the peritoneal cavity following GW9508 administration ( Figure 3 ) in a feed-forward mechanism.…”
Section: Discussionmentioning
confidence: 99%